Prognostic importance of NUP98-rearrangements in acute myeloid leukemia: A systematic review and meta-analysis - Maryam Sheikhi; Payam Siyadat; Mehrdad Rostami; Mohammad Hadi Sadeghian; Elnaz Zahiri; Mohammad Ghorbani; Hossein Ayatollahi; Amirali Ayatollahi; Reza Hemmatan Attarbashi; Zahra Khoshnegah (Caspian Journal of Internal Medicine, 2024)
Background: NUP98 gene fusions in acute myeloid leukemia (AML) have recently attracted much interest. Despite substantial research illuminating the roles of NUP98 fusions in the course of AML, their impacts on the outcome of patients with AML should be explored in more detail. As a result, this meta-analysis was designed to provide further light on the prognostic implications of NUP98 fusions in AML. Methods: We completed an extensive search in PubMed, Scopus, and Web of Science to identify papers evaluating the prognostic effects of NUP98 rearrangements in patients with AML until August 22, 2022. In total, 15 publications with 6142 participants fulfilled the requirements for the current meta-analysis. All the qualified studies were examined for information regarding HRs and 95% confidence interval (95%CI) for overall survival (OS) and event-free survival (EFS). In addition, we utilized Comprehensive Meta-analysis software version 2 (CMA2) for calculating pooled HRs and 95% CI. Results: Our analyses for NUP98-NSD1 indicated that this fusion could significantly impact the outcome of patients with AML (pooled HR: 2.84; 95% CI: 2.49–3.24, P=0.000). Additionally, we observed a strong correlation between NUP98-KDM5A rearrangement and poor prognosis in AML (pooled HR: 2.65; 95% CI: 2.5-2.81; P=0.000). A subgroup analysis also showed that the NUP98-NSD1 and FLT3-ITD together confer a poor prognostic effect (pooled HR: 2.60, 95% CI: 1.61-4.18; P=0.000). Conclusions: NUP98 fusions could significantly impact the outcome of patients with AML. The use of these fusions as prognostic indicators in AML seems rational.